Dante's poets : textuality and truth in the Comedy - Barolini, Teodolinda, 1951- (Princeton legacy library., 1984)
By systematically analyzing Dante's attitudes toward the poets who appear throughout his texts, Teodolinda Barolini examines his beliefs about the limits and purposes of textuality and, most crucially, the relationship of textuality to truth. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.